The determination of the weakest zone and the effects of the weakest zone on the impact toughness of the 12Cr2Mo1R welded joint. (February 2020) - Cao, Rui; Yang, Zhaoqing; Chan, Zhishan; Lei, Wanqing; Li, Jinmei; Zhang, Jianxiao; Liang, Xiaowu; Chen, Jianhong
Abstract: For the actual welded joints, determination of the weakest zone in the welded and the effects of the weakest zone is very important in characterization of the welded joints. In this paper, microstructure feature and charpy toughness of the 12Cr2Mo1R for pressure vessels steel welded joints were systematically investigated. The standard Charpy V-notch impact test specimens were prepared on the base metal, weld metal and various zones of the heat affected zone. The weakest zone of the 12Cr2Mo1R welded joint and its effects on the impact toughness of the welded joint were studied. It shows that at −30 °C, the weakest zone of the welded joint is the coarse-grained heat affected zone (CGHAZ), which impact toughness is 65 J, and its microstructure is composed of a large number of coarse granular bainite and a few blocks ferrite. With the fraction of CGHAZ on the ligament at the notch tip increases, the impact toughness decreases. The closer the CGHAZ location from the notch is, the less the impact toughness of the sample is. Above two aspects fully reflect the effect of the weakest zone on the toughness of the joint. This work reveals the effect of fraction of weakest zone in front of the notch tip on the impact toughness of the 12Cr2Mo1R welded joints.